Indonesian Students' Computational Thinking Performance Based on Level and Gender - Yuni Fitriyah; Wahyudin Wahyudin; Hanifah Nurhayati; Tri Sedya Febrianti (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
Computational thinking (CT) has become an essential competency for students in the 21st century. This study examines the CT proficiency of Indonesian students using data from the Bebras Challenge 2023, an international competition designed to evaluate students' CT skills. The research employs a quantitative ex post facto approach, including a sample of 3,648 students from elementary, junior high, and senior high schools in Indonesia who participated in the Bebras Challenge 2023 and achieved a minimum score of 50. The primary data source for this study is secondary, derived from the Bebras Challenge 2023 test results obtained legally from the official website bebras.or.id, adhering strictly to ethical guidelines regarding participant anonymity. Data analysis techniques include using SPSS 23 software and applying descriptive and inferential statistical methods, specifically the Kruskal-Wallis and Mann-Whitney tests, to examine average score discrepancies across different groups. The findings indicate that CT skills among Indonesian students are significantly underdeveloped, with 87% of participants scoring below the minimum threshold of 50. The average scores of those who exceeded the threshold were around 56.25, indicating room for improvement. Significant disparities in CT abilities were observed among student groups categorized as Siaga, Penggalang, and Penegak, with varying proficiency levels. Additionally, gender-based differences were noted, with male students demonstrating superior CT abilities compared to female students. The study emphasizes the need for collaborative efforts among educators, policymakers, and communities to enhance CT education in Indonesia, advocating for integrated CT curricula, targeted educator training programs, and inclusive learning environments that foster CT skills across all student demographics.